THE USE OF HAAR WAVELETS IN DETECTING AND LOCALIZING TEXTURE DEFECTS - Vaidelienė, Gintarė; Valantinas, Jonas (Image Analysis and Stereology, 2016)
In this paper, a new Haar wavelet-based approach to the detection and localization of defects in grey-level texture images is presented. This new approach explores space localization properties of the discrete Haar wavelet transform (HT) and generates statistically-based parameterized texture defect detection criteria. The criteria provide the user with a possibility to control the percentage of both the actually defect-free images detected as defective and/or the actually defective images detected as defect-free, in the class of texture images under investigation. The experiment analyses samples of ceramic tiles, glass samples, as well as fabric scraps, taken from real factory environment.